DISLOYALTY OF A WIFE IN HAWTHORNE’S THE SCARLET LETTER - Jilly M Kessek; , Mister Gidion Maru; Imelda Lolowang (KOMPETENSI, 2021)
This study is entitled Disloyalty of Wife in The Scarlet Letter By Nathaniel Hawthorne. The aim of this study is to reveal about Disloyalty of Wife in The Scarlet Letter by Nathaniel Hawthorne. The writer employs descriptive approach in conducting this research. The study is entitled Disloyalty of a Wife in The Scarlet Letter By Nathaniel Hawthorne. The aim of this study is to reveal disloyalty of a wife. In order to revealdisloyalty of a wife in this novel, the writer used Deconstruction approach to understanding the relationship between text and meaning. The result of this study revealed that disloyalty is an act that is not god in every relationship. Disloyalty in the novel The Scarlet Letter is revealed in the form being Impatient, breaking the wedding vows, being impure, and the consequence of the decision.